Food Insecurity during COVID‐19. Issue 1 (12th October 2020) - Gundersen, Craig; Hake, Monica; Dewey, Adam; Engelhard, Emily
Abstract: For a decade, Feeding America's Map the Meal Gap (MMG) has provided sub‐state‐level estimates of food insecurity for both the full population and for children. Along with being extensively used by food banks, it is widely used by state and local governments to help plan responses to food insecurity in their communities. In this paper, we describe the methods underpinning MMG, detail the approach Feeding America has used to make projections about the geography of food insecurity in 2020, and how food insecurity rates may have changed due to COVID‐19 since 2018. We project an increase of 17 million Americans who are food insecure in 2020 but this aggregate increase masks substantial geographic variation found in MMG.